PENGARUH PROFITABILITAS DAN SOLVABILITAS PADA AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Dewi, Wulan Paramita; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
The purpose of this study was to determine the effect of profitability and solvency to audit delay, and to determine whether the firms size in the moderating influence of the profitability and solvency to audit delay. This research use signalling theory as a grand theory. This research was conducted on 43 mining company listed on the Indonesia Stock Exchange during the period 2012-2015 with annual financial statements as sekunder method of collecting data. The number of samples are 48, with purposive sampling method. Independent variables used are profitability and solvency. The dependent variable is audit delay. Moderating variables used is firms size. Moderated Regression Analysis as analysis technique. The results showed profitability and solvency has a negative effect on audit delay. Firms size can not moderate profitability in audit delay. Firms size can moderate effect on the solvency of the audit delay.
Keywords: profitability, solvency, firm size, audit delay.